Capturing the Gramscian Project in Critical Pedagogy: Towards a Philosophy of Praxis in Education. Issue 1 (June 2019) - K. P., Manojan
Abstract: As theory and praxis of emancipatory education, critical pedagogy has been profoundly influenced by the ideas of Antonio Gramsci on 'ideology', 'hegemony', 'intellectuals' and 'human consciousness'. The works of Paulo Freire and his critical pedagogy are found analogous in many ways to Gramsci's Marxism specifically in terms of the importance given to cultural action of subalterns. The imperative in critical pedagogy is to construct counter-hegemonic positions against the imperatives of the dominant class agenda of limiting subalterns from entering into the making of history. As a praxis it aims at unravelling the potentialities within subalterns through their wisdom, practical knowledge and everyday common sense and thereby transforming educational regimes as spaces of social justice and human liberation. This article attempts to capture the contours of critical pedagogy and explores how Gramsci's Marxism has influenced the formation of critical pedagogy and its intellectual trajectories.